Tibetan Bonpo Mendrup: The Precious Formula’s Transmission - Sehnalova, Anna (History of Science in South Asia)

(untitled) (University of Alberta Library, 2017)
The article presents the traceable history of the Tibetan Bonpo mendrup ritual practice in textual sources, as it has been recorded by the Bonpos themselves. These records are put into context with the current performance of the practice by the Bonpo exile community.The study aims to embrace all the relevant Bonpo historical material accessible, and thus deals with documents of a wide time spam, from the eleventh or twelfth century onwards until the early twentieth century. The Bonpo mendrup is a healing, longevity, rejuvenation and enlightenment-seeking contemplative meditational practice of the Tibetan tantric tradition with a strong emphasis on its medicinal component. It embodies various spheres of knowledge and their principles, as the Indian tantrism, a strong Buddhist cosmological organisational and soteriological framework, the Tibetan medical tradition, with embedded elements of alchemy and Tibetan indigenous religious notions. As the studied sources reveal, its origin can be traced to the intellectually vibrant times in Tibet of around the twelfth century, where all these fields of expertise came together. Thus the case provides an example of such a complex composed of tantra, medicine and alchemic influences specific for Tibet.Since then, the Bonpo mendrup can be followed by varied records in a number of Bonpo literary sources of different genres. These are compared with the present form of the ritual. The sources support the ritual’s anticipated transmission and practice throughout the history. They show that different ideas apply to its origin, and particularly its revelation as a treasure text, and that the ritual existed in varied forms, and was shared and imparted among different lineages of Bon. The most important finding is that the practice is actually traceable throughout the history, and likely have never ceased to be active over the centuries from the very early times until today.